Differentiating iron deficiency anaemia and β thalassemia trait based on red cell indices- an economic way to health care in a resource limited setup - J. Odhwani, Mansi; K. Dholakia, Spruha; G. Kangad, Meera; A. Vachhani, Nishith; B. Colah, Roshan; L. Nandani, Sanjiv; J. Vekariya, Daya; N. Kashiyani, Heena (International Journal of Research in Medical Sciences, 2025)
Background: In a developing country like India, anaemia is a significant health burden. Specific cost-effective methods for screening of β-thalassemia trait (BTT) should be adopted to differentiate from iron deficiency anemia (IDA) with the use of various indexes derived from red blood cell (RBC) indices. Methods: A total of 845 adults were screened for carrier detection of β thalassemia during May to July, 2024. A complete hemogram and HPLC analysis for thalassemia was done on all the samples. Serum ferritin was estimated in samples with MCV<78 fl and MCH<27 pg. Different discriminant functions like Mentzer index (MI), Shine and Lal (S and L) index, red cell distribution width index (RDWI) and red cell distribution width (RDW) were used. Results: Of the 135 individuals, 80 individuals had iron deficiency anaemia (IDA). 17 individuals had β-thalassemia trait (BTT), 19 had coexistent IDA and BTT, 8 individuals had other haemoglobinopathies; 11 individuals had normal ferritin with normal HbA2 levels. RBC count was higher in BTT as compared to IDA cases (p value <0.001). MI and S and L index showed 97.20% and 83.78% sensitivity (p value <0.01); RDWI and MI showed 96.15% and 92.4% specificity value (p value <0.01) while RDWI and MI had 91.23% and 89.66% (p value <0.01) accuracy for detection of BTT. Conclusions: Combination of these two indices, MI and RDWI with final confirmation by HPLC would help to reduce the overall cost of screening in situations where the ideal screening approach of doing CBC and HPLC analysis of all individuals as a first step itself is not possible due to cost constraints.